Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve the problem step-by-step:
### Step 1: Understanding the Geometric Series (G.S.)
In a geometric series, each term after the first is found by multiplying the previous term by a constant called the common ratio, denoted as [tex]\( r \)[/tex]. The [tex]\( n \)[/tex]-th term [tex]\( T_n \)[/tex] of a geometric series can be represented as:
[tex]\[ T_n = a \cdot r^{n-1} \][/tex]
where [tex]\( a \)[/tex] is the first term.
### Step 2: Representing Given Terms in the Formula
We are given:
- The 3rd term ([tex]\( T_3 \)[/tex]) is 27:
[tex]\[ T_3 = a \cdot r^2 = 27 \][/tex]
- The 5th term ([tex]\( T_5 \)[/tex]) is 3:
[tex]\[ T_5 = a \cdot r^4 = 3 \][/tex]
### Step 3: Finding the Common Ratio [tex]\( r \)[/tex]
To find the common ratio [tex]\( r \)[/tex], we can divide the equation for the 5th term by the equation for the 3rd term:
[tex]\[ \frac{a \cdot r^4}{a \cdot r^2} = \frac{3}{27} \][/tex]
Simplifying this, we get:
[tex]\[ r^2 = \frac{1}{9} \][/tex]
[tex]\[ r = \frac{1}{3} \][/tex]
(Note: We take the positive value for [tex]\( r \)[/tex] as we're dealing with a standard geometric series.)
### Step 4: Finding the First Term [tex]\( a \)[/tex]
With [tex]\( r \)[/tex] found, we substitute it back into the equation for the 3rd term to find [tex]\( a \)[/tex]:
[tex]\[ a \cdot \left(\frac{1}{3}\right)^2 = 27 \][/tex]
[tex]\[ a \cdot \frac{1}{9} = 27 \][/tex]
[tex]\[ a = 27 \cdot 9 \][/tex]
[tex]\[ a = 243 \][/tex]
### Step 5: Find the Term Which is [tex]\( \frac{1}{9} \)[/tex]
We want to find the term [tex]\( T_n \)[/tex] which equals [tex]\( \frac{1}{9} \)[/tex]. Using the formula for the [tex]\( n \)[/tex]-th term:
[tex]\[ a \cdot r^{n-1} = \frac{1}{9} \][/tex]
Substitute [tex]\( a = 243 \)[/tex] and [tex]\( r = \frac{1}{3} \)[/tex] into the equation:
[tex]\[ 243 \cdot \left(\frac{1}{3}\right)^{n-1} = \frac{1}{9} \][/tex]
### Step 6: Simplifying the Equation
[tex]\[ \left(\frac{1}{3}\right)^{n-1} = \frac{1}{2187} \][/tex]
Since [tex]\( 243 \cdot 9 = 2187 \)[/tex], and knowing [tex]\( (1/3)^7 = 1/2187 \)[/tex]:
[tex]\[ (1/3)^{n-1} = (1/3)^7 \][/tex]
Thus:
[tex]\[ n-1 = 7 \][/tex]
[tex]\[ n = 8 \][/tex]
### Conclusion
Therefore, the term in the geometric series that equals [tex]\( \frac{1}{9} \)[/tex] is the 8th term.
### Step 1: Understanding the Geometric Series (G.S.)
In a geometric series, each term after the first is found by multiplying the previous term by a constant called the common ratio, denoted as [tex]\( r \)[/tex]. The [tex]\( n \)[/tex]-th term [tex]\( T_n \)[/tex] of a geometric series can be represented as:
[tex]\[ T_n = a \cdot r^{n-1} \][/tex]
where [tex]\( a \)[/tex] is the first term.
### Step 2: Representing Given Terms in the Formula
We are given:
- The 3rd term ([tex]\( T_3 \)[/tex]) is 27:
[tex]\[ T_3 = a \cdot r^2 = 27 \][/tex]
- The 5th term ([tex]\( T_5 \)[/tex]) is 3:
[tex]\[ T_5 = a \cdot r^4 = 3 \][/tex]
### Step 3: Finding the Common Ratio [tex]\( r \)[/tex]
To find the common ratio [tex]\( r \)[/tex], we can divide the equation for the 5th term by the equation for the 3rd term:
[tex]\[ \frac{a \cdot r^4}{a \cdot r^2} = \frac{3}{27} \][/tex]
Simplifying this, we get:
[tex]\[ r^2 = \frac{1}{9} \][/tex]
[tex]\[ r = \frac{1}{3} \][/tex]
(Note: We take the positive value for [tex]\( r \)[/tex] as we're dealing with a standard geometric series.)
### Step 4: Finding the First Term [tex]\( a \)[/tex]
With [tex]\( r \)[/tex] found, we substitute it back into the equation for the 3rd term to find [tex]\( a \)[/tex]:
[tex]\[ a \cdot \left(\frac{1}{3}\right)^2 = 27 \][/tex]
[tex]\[ a \cdot \frac{1}{9} = 27 \][/tex]
[tex]\[ a = 27 \cdot 9 \][/tex]
[tex]\[ a = 243 \][/tex]
### Step 5: Find the Term Which is [tex]\( \frac{1}{9} \)[/tex]
We want to find the term [tex]\( T_n \)[/tex] which equals [tex]\( \frac{1}{9} \)[/tex]. Using the formula for the [tex]\( n \)[/tex]-th term:
[tex]\[ a \cdot r^{n-1} = \frac{1}{9} \][/tex]
Substitute [tex]\( a = 243 \)[/tex] and [tex]\( r = \frac{1}{3} \)[/tex] into the equation:
[tex]\[ 243 \cdot \left(\frac{1}{3}\right)^{n-1} = \frac{1}{9} \][/tex]
### Step 6: Simplifying the Equation
[tex]\[ \left(\frac{1}{3}\right)^{n-1} = \frac{1}{2187} \][/tex]
Since [tex]\( 243 \cdot 9 = 2187 \)[/tex], and knowing [tex]\( (1/3)^7 = 1/2187 \)[/tex]:
[tex]\[ (1/3)^{n-1} = (1/3)^7 \][/tex]
Thus:
[tex]\[ n-1 = 7 \][/tex]
[tex]\[ n = 8 \][/tex]
### Conclusion
Therefore, the term in the geometric series that equals [tex]\( \frac{1}{9} \)[/tex] is the 8th term.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.